A Review on Flavonoids as a Potential Biomolecule for Inhibiting the Effect of Head and Neck Cancer - Ikram, Sara; Ashraf, Muhammad Moazzam; Hussain, Mudasir; Shaheen, Sidra; Shaoib, Muhammad (Archives of Advances in Biosciences, 2024)
Context: Cancer is one of the most significant, complex, and long-term diseases, characterized by uncontrolled cell multiplication, affecting millions of people around the globe. Developed countries are considered to experience higher incidence and mortality rates due to cancer. Cancer affects various body parts including the liver, breast, lungs, bladder, rectum, prostate, blood, and head and neck. Head and neck cancer is the seventh most prevalent cancer globally, typically arising from tissues of the mouth, larynx, pharynx, trachea, throat, and salivary glands. Evidence Acquisition: Different factors can cause cancer, such as the use of tobacco, alcohol, genetic alterations, and other environmental factors. Treatment is a challenging part due to the disease’s progression and potential side effects on normal body functions. Current treatments such as chemotherapy have limitations due to their toxic effects on other normal body cells. Therefore, the need for less toxic and more selective treatment arises. Natural phenolic compounds, such as flavonoids derived from plants, fungi, and bacteria, have shown promising potential in the treatment due to a higher therapeutic index and low toxicity level. Flavonoids reduce cancer cell growth, inhibit cancer development enzymes, and regulate apoptosis-related proteins, transcription factors, and pathways. Several studies have shown that their anti-cancer properties have made them effective against head and neck cancer cells. Results: Plants have been major sources of flavonoids but fungi, especially endophytic fungi are also valuable sources of natural therapeutic agent flavonoids. Extraction of flavonoids from fungi offers a sustainable and environmentally friendly approach, eliminating the need for land, water, and fertilizer. Furthermore, fungi can yield higher amounts of flavonoids than other sources. Conclusion: Further research in medical applications of flavonoids as biological therapeutic agents could potentially reduce the impact of the disease.